Filologinis Aleksandro Luočio salto: Трумпасъ Kатехизмасъ (1865) verčiamas Trumpu Katechizmu (1874) - Subačius, Giedrius (Baltistica, 2006)
The philological somersault of Aleksandras Luotys: Трумпасъ Катехизмасъ (1865) into Trumpas Katechizmas (1874)Aleksandras Luotys transliterated his Lithuanian manuscript – the Catholic Brief Catechism (Trumpas Katechizmas, 1874; LLTIB: f. 1 3468) – from the variant in Cyrillic characters Трумпасъ Катехизмасъ of 1865 (first prepared in manuscript in Latin characters by the bishop Motiejus Valančius and later printed in Cyrillic letters by Jonas Krečinskis). In the history of Lithuanian Luotys’ manuscript was unique in the sense that it was the only known Lithuanian text in Latin letters transcribed from the Cyrillic Lithuanian version, which was then required by the Russian officials.It is obvious that Luotys transcribed the Cyrillic text entirely, and that he did not intend to shorten it in any planned manner. Still, most probably due to his absentmindedness, Luotys omitted some lines of the original in several places.Luotys made certain changes in his transliterated manuscript. For instance, he changed the Orthodox formula for making the sign of the cross into the Catholic one. He edited some grammatical forms and some stylistic features. Luotys also changed certain words – he ignored some of Valančius’ attempts to modernize religious terminology and he used the traditional religious terms or words instead of those proposed by Valančius (e.g. he changed кончесъ ‘passion, suffering’ into mukas ‘ibid.’; рижимосъ ‘determination’ into pastanawiejemu ‘ibid.’; касдениней ‘daily’ into pawʒedni ‘ibid.’).Luotys corrected some typographical errors but erred himself as well.He changed certain Highland Lithuanian dialectal features into the Lowland Lithuanian (dounininkai in particular) equivalents. Cf. [ẹi] in Luotys’ text (вена ‘one’ –> wejna); [ọu] (дуону ‘bread’ instr. sg. –> downo); , , [ẹ] (бути ‘to be’ –> buty, бути ‘ibid.’ bute, пагимде ‘(she) gave birth’ –> pagemdi); [ọ] (ишгульдимасъ ‘explanation’ –> iʒgoldimas); žem. [ie] (галету ‘(he/she) could’ galietu); -yms (висѣмсъ ‘for everyone’ –> wisyms); [ọn] (дангаусъ ‘of heaven’ –> dongaws); [t] (аукщяусъ ‘higher’ –> awkʒtews); cond. 3 [ọm] (атпиркту ‘(he/she) would redeem’ –> atperktom). There were many cases of Lowland dialectal peculiarities. Thus, Luotys’ text was based on the Lowland dialect much more than on the Cyrillic prototype.There were almost no cases, however, of substitution in the opposite direction – Lowland features were almost never changed into the Highland equivalents.Judging by the way Luotys edited the text one can assume that the manuscript was not prepared for the purpose of publication, and that Luotys needed it in Latin letters for his personal uses. Therefore Luotys edited some phrases of the prototype freely, and introduced more of his native Skuodas dialect features (from the Northwestern Lowland territory).Luotys also used certain specific orthographical peculiarities. Quite often he chose the character even before [e], [ẹ], and [i] vowels (апмислити ‘to think of’ –> apmisłiti; кяле ‘of the road’ gen. sg. –> kieły). Luotys selected the letter to convey the second component in the diphthongs [au], [ọu], cf. , , and . He always wrote the long letters to express the digraph . Those orthographic features were well known in eighteen-century Lithuanian (approximately one hundred years before Luotys produced his transcript). Thus, Luotys adopted much older orthography. In particular, Luotys’ orthographical features resembled certain features of Žyvatas of 1759. It is possible to assume that Luotys might have learned to read and write from this or from any of the other multiple editions of Žyvatas. Generally, judging by the inconsistency in orthography it is evident that Luotys wasn’t a skilled writer in Lithuanian (cf. Wysopermo ‘first of all’).
Keywords: senieji raštai